Green Infrastructure Investment Governance: A Literature Review and Lesson for Indonesia - Azaki, Naufal; Lutfi, Achmad (Technium Social Sciences Journal, 2022)
Green and climate resilience infrastructure have received widespread attention because of their central role in climate change adaptation and mitigation. Many works of literature emphasize the importance of climate governance, primarily in terms of funding. On the other hand, the world faces a funding gap because government spending cannot fully support infrastructure needs. This underlies the need for private participation in infrastructure development, especially green infrastructure, to address climate change. This study uses a qualitative approach with a literature review method on various related literature and refers to the framework of Corfee-Morlot et al. (2012) and aims to analyze the policy dynamics, governance, and instruments needed as lessons for Indonesia. The green infrastructure investment policy framework can be developed through 5 (five) main approaches; alignment of policy goals and targets, policies that enable investment to grow through incentives, development of investment schemes/financial instruments, strengthening the alternative resources and institutional capacities, and promotion of the importance of green investment.